USAGE OF PHRASEOLOGISM WITH VERB MEANING IN FOLK LEGENDS OF KARAKALPAK (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Legends have a special place among the folklore works with their rich idea-theme. Karakalpak folklore legends have become the research object of a number of folklore scientists, and now its study from linguistic point of view is one of the actual issues of today. The meaning features of the verb phraseologisms in the Karakalpak language are very complicated. The stable phrases consisted of verbs which is the part of speech are mainly used in folkloric works, including in the language of legends, in various meanings and services. Therefore, in this article, we learned about the usage features of the verb phraseologisms in Karakalpak folk legends.